PENGARUH ADOPSI PSAK NO.24 TERHADAP EARNINGS RESPONSE COEFFICIENT - Refyal, Ilha; Martani, Dwi (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
This study aims to analyze the influence of PSAK No.24(Revisi 2004) adoption on earningsresponse coefficient (ERC). This study focuses discussion on the differences of ERC between theperiod before to the period after the adoption, the influence of changes in the post-employmentbenefits account (due to revision) to the ERC, and the influence of the difference in time ofadoption to the ERC. This study is divided into two tests, which are panel data regression testingand Multiple Cross-section Regression testing. ERC in the period after the adoption of the PSAK24 revision is greater than the period before the adoption of PSAK 24 revision. By usingmanufacturing companies during that adoped PSAK 24 during 2004 or 2005, the research findthat changes in post-employment benefits liability have a significant positive effect on ERC. Thecompanies that adopt the standard earlier (early adopter) have a greater ERC compare to thecompanies that adopt at the end of the mandatory time (late adopter) The study also supportsprevious research on factors affecting the ERC, which are the capital structure and size.Keywords:Earnings Response Coefficient, Revision PSAK 24, Post-employment Benefits Liability,Adoption Timing.